The Influence of Brand Image, Digital Advertising, Influencer Credibility, and Customer Trust on the Online Purchase Intention of Generation Z in Yogyakarta - Agus Mulyono; Danang Sunyoto (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the influence of brand image , digital advertising , influencer credibility , and customer trust on online purchase intention among Generation Z in Yogyakarta. The background of this study is based on the increasing online shopping activity among the younger generation who are highly exposed to digital technology and social media. The research method used is a quantitative approach with data collection through questionnaires distributed to Generation Z respondents aged 18–26 years who are active online shoppers in Yogyakarta. Data analysis was conducted using multiple linear regression to test the relationship between variables. The results showed that the four independent variables have a positive and significant effect on online purchase intention . This finding confirms that a strong brand image, relevant digital advertising, high influencer credibility, and good consumer trust are key factors in increasing online purchase intention among Generation Z. This study provides strategic implications for business actors in designing digital marketing strategies that are more adaptive to the characteristics of young consumers in the digital era.